2018
DOI: 10.25066/agrotec.v39i1.37822
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of flower traits in ornamental pepper

Abstract: Diallel crosses provide estimates of useful parameters in the selection of parents for hybridization. They also help in understanding the gene action behind the determination of characters of interest. The objective of this study was to determine the genetic control of flower traits in ornamental pepper based on a complete diallel with parents F1’s and reciprocal crosses. The experiment was conducted in a greenhouse at Laboratório de Biotecnologia Vegetal, Centro de Ciências Agrárias, Universidade Federal da P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The additive effects of the genes have been predominant for most of the flower characteristics and the non-additive effects were higher only for the days for flowering character. In relation to this, Pessoa et al [28] found that the additive effects influenced the performance of the hybrids for the characteristics of flowers in ornamental pepper. Santos et al [29] in a study with C. annuum for ornamental pepper, found a similar result to that work, and identified the control of the additive effects for the characteristic corolla diameter.…”
Section: Discussionmentioning
confidence: 98%
“…The additive effects of the genes have been predominant for most of the flower characteristics and the non-additive effects were higher only for the days for flowering character. In relation to this, Pessoa et al [28] found that the additive effects influenced the performance of the hybrids for the characteristics of flowers in ornamental pepper. Santos et al [29] in a study with C. annuum for ornamental pepper, found a similar result to that work, and identified the control of the additive effects for the characteristic corolla diameter.…”
Section: Discussionmentioning
confidence: 98%
“…In order for one to make the accessions of a germplasm bank available for use in improving characteristics and launching new cultivars, it is essential that they be properly described [16,17]. In this sense, Capsicum germplasm characterization studies have been based on predictive methods that take into account agronomic, physiological, morphological, bromatological, and molecular descriptors [18][19][20][21]. The study of morphological characters associated with molecular markers has been used by many studies because they provide more accurate genetic information of the genotypes studied [22].…”
Section: Introductionmentioning
confidence: 99%